New Normal Adaptation (NNA) Relationship with The Quality Of Life Hemodialysis Patients During The Covid-19 Pandemic At Lamongan Muhammadiyah Hospital - Rusulustin Mustikaria; Ika Yuni Widyawati; Harmayetty Harmayetty (Critical Medical and Surgical Nursing Journal (CMSNJ), 2022)
Introduction: The quality of life of patients with Chronic Kidney Disease (CKD) who got hemodialysis had decreased along with the increasing level of the disease, which caused problems of patient productivity. During the pandemic, hemodialysis patients were at very high risk of exposure to covid-19, it was very important to implement New Normal Adaptation to reduce morbidity and mortality. The purpose of this study was to explain the relationship between New Normal Adaptation and the life quality of hemodialysis patients during the pandemic of COVID-19 at Lamongan Muhammadiyah Hospital. Methods: This study used a correlation design, by simple random sampling technique, the population was 85 respondents. The samples were 70 respondents in the Hemodialysis room at Lamongan Muhammadiyah Hospital which was in the inclusion criteria. The data that was collected included respondent characteristics, New Normal Adaptation, and quality of life, the data collection used the Google questionnaire form, then it was analyzed using the Spearman test.  Results: Some of the respondents were treated as new normal in the moderate category, most of the respondents had life quality in the bad category and there was a relationship between New Normal Adaptation with the life quality of hemodialysis patients, the significant value was = 0.303 and p = 0.011. Conclusion: During the pandemic, health education activities for hemodialysis patients could use social media (Facebook, Instagram, Twitter, Whatsapp) that would increase New Normal Adaptation at home and in the hospital. So that, the quality of the patient's life would be good.